Hubungan Pengetahuan, Sikap dan Sosial Budaya Ibu Rumah Tangga dengan Pelaksanaan PHBS di Desa Inelika Kecamatan Bajawa Utara Kabupaten Ngada - Kristina Bupu; Marylin S. Junias; Agus Setyobudi (Media Kesehatan Masyarakat, 2021)
Clean and healthy living behavior is one of the factors causing disease transmission if not executed properly. Inelika Village is the village that has the lowest clean and healthy lifestyle. This is because the community has not implemented a clean and healthy lifestyle programs that has been implemented by health workers. This research aim is to determine the relationship between knowledge, attitudes and socio-culture of housewives with the implementation of clean and healthy family behavior in Inelika Village.This study was an analytic observational study with a cross sectional study design. The population in this study were 185 housewives. The sample used in this study was 65 people, using the proportional random sampling method. Data were analyzed using Chi-square test. The results showed that there was a significant relationship between attitudes (0.002), socio-culture (0.031) and the implementation of clean and healthy living behavior. There is no relationship between knowledge and the implementation of clean and healthy living behavior (0.569). There must be cooperation between the government and the local community to improve the existing hygiene and healthy lifestyle programs.